A novel permanent magnet flux switching machine with an outer-rotor configuration for in-wheel light traction applications - Fei, Wei-Zhong; Luk, Patrick Chi-Kwong; Shen, Jian-Xin; Wang, Yu; Jin, Meng-Jia (Institute of Electrical and Electronics Engineers (IEEE), 2012)
This paper proposes a novel permanent magnet flux switching (PMFS) machine with an outer-rotor configuration for in-wheel light traction applications. The geometric topology of the outer-rotor PMFS machine is introduced and the analytical sizing equations are derived to determine the main design parameters of the machine. Two-dimensional (2-D) Finite element analysis (FEA) models are developed to investigate and optimize the machine performance. Furthermore, the flux weakening capability of the machine is analyzed and further improved by segmental permanent magnets with iron bridges. The machine performance predictions by 2-D FEA models are validated by experimental tests on the prototype machine. The suitability of the proposed outer-rotor PMFS machine for in-wheel light traction application is demonstrated.